THE DYNAMICS OF THE GLOBAL ECONOMY IN THE SHADOW OF WAR CRIMES:INTEGRATING GEOPOLITICAL, SOCIAL, AND ECONOMIC FACTORS: A LITERATURE REVIEW STUDY - Adi Mursalin; Peringatan Harefa; Ahmad Rizani; Nani Hamdani Amir; Otanius Laia (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This literature review explores the intricate interplay between war crimes and the global economy, integrating geopolitical, social, and economic factors. Delving into historical perspectives, the study analyzes how geopolitical dynamics shape the perpetration of war crimes and influence economic consequences. Societal implications, including humanitarian crises and social unrest, are scrutinized, revealing the profound and lasting consequences on affected communities. The economic factors section dissects the repercussions of armed conflicts, examining impacts on infrastructure, productivity, and the role of multinational corporations. The integration of these factors underscores a complex web of interactions shaping the aftermath of war crimes. Case studies provide real-world examples, offering lessons for post-conflict recovery, while methodological approaches assess research methodologies and identify opportunities for further investigation. This review contributes a comprehensive understanding of the intricate relationships between war crimes and the global economy, offering valuable insights for scholars, policymakers, and practitioners navigating the complex terrain of post-conflict recovery and global stability.